THE EFFECT OF ETHICAL LEADERSHIP ON VOICE BEHAVIOR: THE ROLE OF MEDIATORS ORGANIZATIONAL IDENTIFICATION AND MODERATING SELF-EFFICACY FOR VOICE - Utami Tunjung Sari (Journal of Leadership in Organizations, 2019)
Some ethical violations that occur in both business organizations and the government in turn highlight the important role of leadership in managing ethical accountability. Ethical leadership arises as a result of various ethical violations and demands for leaders to be able to manage ethical accountability. This study explains the mechanism of influence of ethical leadership behavior on voice behavior in private sector organizations in Indonesia. This study attempts to look at the role of organizational identification as a mediator on the influence of ethical leadership on voice behavior and incorporate the effects of mediation and moderation in one model (moderated mediation model) by using self-efficacy for voice as moderating. Learning theory, social exchange, social identity, and self-efficacy were used as the foundation in this study. 230 valid responses from employees took part in this study. The results of the data analysis showed ethical leadership behavior had a positive influence on voice behavior. Furthermore, organizational identification mediates the influence of ethical leadership on voice behavior and self-efficacy for voice moderating that influence. These findings indicate that employees identified with the organization have a tendency to voice behavior, then employees with high self-efficacy for voice will be more confident in their ability to conduct voice behavior.